Cut‐offs for calf circumference as a screening tool for low muscle mass: WASEDA'S Health Study. Issue 10 (4th September 2020) - Kawakami, Ryoko; Miyachi, Motohiko; Sawada, Susumu S.; Torii, Suguru; Midorikawa, Taishi; Tanisawa, Kumpei; Ito, Tomoko; Usui, Chiyoko; Ishii, Kaori; Suzuki, Katsuhiko; Sakamoto, Shizuo; Higuchi, Mitsuru; et al.
Abstract : Aim: To re‐evaluate the suitability of calf circumference as a surrogate marker of low muscle mass measured by both bioelectrical impedance analysis (BIA) and dual‐energy X‐ray absorptiometry (DXA). We also examined the effects of obesity and age on low muscle mass screening using calf circumference. Methods: In total, 1239 adults participated in this cross‐sectional study. We measured the maximum calf circumference in a standing position and appendicular skeletal muscle mass (ASM) using BIA and DXA. We defined low muscle mass based on the Asian Working Group for Sarcopenia 2019 consensus. Results: Calf circumference was positively correlated with BIA‐measured ASM/height 2 (men: r = 0.81, women: r = 0.73) and DXA‐measured ASM/height 2 (men: r = 0.78, women: r = 0.76). In the subgroup analyses by obesity and age, calf circumference was also positively correlated with ASM/height 2 . The optimal calf circumference cut‐offs for low muscle mass screening measured by BIA and DXA were 35 cm (sensitivity 91%, specificity 84%) and 36 cm (sensitivity 82%, specificity 80%) for men, and 33 cm (sensitivity 82%, specificity 84%) and 34 cm (sensitivity 85%, specificity 72%) for women, respectively. Conclusions: Calf circumference is positively correlated with BIA‐ and DXA‐measured muscle mass regardless of obesity and age and is a simple and accurate surrogate marker of muscle mass for diagnosing sarcopenia. Geriatr Gerontol Int 2020; 20: 943–950 .